Biogeochemistry of the Atmosphere, Ice and Water of the White Sea The White Sea Environment Part I (The Handbook of Environmental Chemistry,, 2018)
This book is devoted to the biogeochemical environment of the White Sea, an inland sea in the Northwestern region of Russia. It provides a comprehensive review and discusses the latest research findings on the oceanology, sedimentology and biogeochemistry of the White Sea water column. The topics discussed include the regulation of the physico-geographical conditions in the White Sea basin; dispersed sedimentary substance of the atmosphere and the cryosphere; the geochemical peculiarities of the river discharge into the White Sea; and the phyto- and zooplankton activities in the White Sea. Taking the biggest river in the White Sea basin as an example, the authors closely examine the deposition of suspended particulate matter, the biogeochemical behaviour of dissolved and suspended forms of organic material and the significant group of chemical elements in the river-sea mixing zone of the Severnaya Dvina River. The book ends with a summary of the key conclusions and recommendations. Together with the companion volume Sedimentation Processes in the White Sea: The White Sea Environment Part II, it offers an essential source of information for postgraduate students, researchers and stakeholders alike.